Foreign trade: say it with flowers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Kenya's flower exports to Europe now count alongside tea, coffee, cotton and sugar as major exports. The Kenya Flower Council expects that the final level of exports in 1998 will exceed $90 million, with annual growth at 10%. In 1997, roses...